Ruud van Empel : the Office - Fernández, Mariona (CV Photo, 2000)
The Office, produced using digital photo-editing techniques, arises from the unreal. Ruud van Empel combines many of the avant-garde influences that have liberated photography from its obligation to the truth through the invention of montage. At the same time that these avant-gardes and ideas about progress were developing, the office became widespread as a space of production of the impalpable. These offices reflect the inferiority and solitude of their inhabitants, defined by eclectic collections of objects.